The messages of the books of the Bible ; v. 3 - Morgan, George Campbell, 1863-1945 (London, UK Hodder and Stoughton)
Contents : v. 3 : Matthew - Colossians
Keywords: Bible. N.T. Gospels -- commentaries; Bible. N.T. Acts -- commentaries; Bible. N.T. Epistles of Paul -- commentaries